Deadlock The Inside Story Of America's Closest Election - The Washington Post (New York PublicAffairs, 2001)
Offers an account of the post-election fight for the White House, including the debate over hanging and pregnant chads, butterfly ballots, manual recounts, and the U.S. Supreme Court's role in the conclusion of the election.
Keywords: Nonfiction; History; Politics